1996
DOI: 10.1016/s0006-3495(96)79452-3
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of phospholipid vesicles by water-soluble polymers

Abstract: Water-soluble polymers such as dextran and polyethylene glycol are known to induce aggregation and size growth of phospholipid vesicles. The present study addresses the dependence of these processes on vesicle size and concentration, polymer molecular weight, temperature, and compartmentalization of the vesicles and polymers, using static and dynamic light scattering. Increasing the molecular weight of the polymers resulted in a reduction of the concentration of polymer needed for induction of aggregation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…There were no significant differences thereafter. Dextran probably improves adsorption rate by promoting fusion of phospholipid membranes [17,18], but does not influence equilibrium surface tension under the present experimental conditions. During quasistatic surface compression, dextran also lowered Á min .…”
Section: Discussionmentioning
confidence: 60%
“…There were no significant differences thereafter. Dextran probably improves adsorption rate by promoting fusion of phospholipid membranes [17,18], but does not influence equilibrium surface tension under the present experimental conditions. During quasistatic surface compression, dextran also lowered Á min .…”
Section: Discussionmentioning
confidence: 60%
“…This fi nding suggests that differences in polymer effects may occur because of [10,11] although dextran aerosolized into lungs with milk aspiration injury before surfactant treatment, enhances surfactant responses [28] . PEG and dextran induce aggregation of pure lipids [29,30] and we have found that PEG and dextran both increase aggregation of surfactants, a fi nding associated with increased rates of adsorption of surfactant lipids to the surface [31] . Depletion forces acting on lipid vesicles are increased in the presence of polymers, which can enhance rates of adsorption of surfactants from subphase to alveolar surface [15,20] .…”
Section: Discussionmentioning
confidence: 81%
“…Both experimental (5,6) and theoretical (28) studies support the notion that the nonionic polymers improve the surface activity of lipid extract surfactant by a depletion-attraction mechanism. It has been demonstrated that in a pure phospholipid vesicle system, PEG at certain molecular weights and concentrations can induce a depletion-attraction force that promotes the formation of large phospholipid aggregates (30). Large aggregates are known to be more surface active than their smaller counterpart both in vitro (31) and in vivo (32).…”
Section: Discussionmentioning
confidence: 99%